Tvorba korpusů mluveného jazyka: Miloslav Vondráček (Stanje in perspektive uporabe govornih virov v raziskavah govora, 2024)
Creation of Spoken Language Corpora. In recent years, my former university has been involved in the creation of corpora of spoken communication. The students made audio recordings of 220 private conversations. With my help, the students converted these dialogues into written text. On this occasion, we had to solve some practical problems. These difficulties led to the formulation of substantial theoretical questions. The relativity of the units of spoken language is one of the fundamental ones. The result is a corpus building methodology that has been continuously improved since then. The paper provides an overview of the fundamental questions and attempts to provide theoretical answers and a solution methodology. Má někdejší univerzita se v minulých letech podílela na tvorbě korpusů mluvené komunikace. Spolu se studenty jsme pořídili zvukový záznam 220 soukromých dialogických situací a jejich přepis. Při té příležitosti jsme museli řešit řadu praktických problémů. Ty vedly k formulaci podstatných teoretických otázek. K základním patří relativita jednotek mluveného jazyka. Výsledkem je metodologie tvorby korpusu, od té doby neustále zdokonalovaná. Příspěvek přináší přehled základních otázek a snaží se poskytnout teoretické odpovědi i metodiku řešení.